(untitled) (Journal of Pharma Insights and Research, 2025)
G protein-coupled receptors (GPCRs) represent the largest class of membrane proteins and the most common target of approved pharmaceuticals. Classical pharmacology categorizes ligands based on a linear model of efficacy, yet this fails to account for the pluri-dimensional nature of GPCR signaling. These receptors do not function as simple monoliths but as allosteric machines capable of activating multiple, distinct downstream pathways, primarily mediated by heterotrimeric G proteins or β-arrestins. Biased agonism, or functional selectivity, describes the ability of a ligand to stabilize a specific receptor conformation that preferentially engages one signaling pathway over others. This selectivity is not inherent to the receptor alone but is dictated by the dynamic, spatio-temporal assembly of a macromolecular complex known as the signalosome. This complex, composed of the receptor, transducers, scaffolding proteins, kinases, and effectors, translates the ligand-receptor interaction into a specific cellular phenotype. Biased agonists offer a promising strategy for developing a new generation of medicines by selectively activating pathways associated with therapeutic benefit while avoiding those linked to adverse effects such as G protein-mediated analgesia over β-arrestin-mediated respiratory depression at the μ-opioid receptor. This approach requires a sophisticated knowledge of signalosome composition and the structural basis of ligand-receptor-transducer interactions to rationally design therapeutics with superior efficacy and improved safety profiles